West African Youth Challenges and Opportunity Pathways - McLean, Mora L. (Gender and Cultural Studies in Africa and the Diaspora,, 2020)
This open access edited collection explores obstacles that impede, and potential pathways toward improving, the material and psychological well-being of youth in and from West Africa. Contributors range from researchers to practitioners, offering a transatlantic, transcontinental set of perspectives on the mounting evidence that, whether they reside in poor "underdeveloped" or wealthier (OECD) countries, young people who live in poverty and are African-born or of African descent are disproportionately burdened by the global phenomenon of increasing income inequality. Mora McLean is Co-Adjutant in the Office of the Chancellor and Office of Globally Engaged Experiential Learning at Rutgers, The State University of New Jersey, USA.